FLORISTIC DIVERSITY AND CHOROTYPE ANALYSIS OF TERICH VALLEY CHITRAL: A CONTRIBUTION TO THE FLORA OF HINDUKUSH RANGE, NORTHERN PAKISTAN - A. Zaman; L. Badshah (Journal of Animal and Plant Sciences, 2021)
Terich valley in district Chitral, Hindukush Range, being a remote area remained unexplored regarding plant resources. The present study was conducted during 2017-2019 in different seasons for the documentation of species diversity, phyto-climatic spectrum and Chorotype. Floristic inventory of the study area showed that there were 445 species belonging to 272 genera and 71 families. The ecological adaptation of plant species was determined using Raunkiaer's method and chorotype by indispensible references.The dominant families were Asteraceae (88 Species, 19.73%), Poaceae (49 Species, 10.73%), Papilionaceae (34 Species, 7.6%) and Brassicaceae (30 Species, 6.62%). Among the exsiting genera there were 29 monotypic genera, 11 genera with two species, 10 genera with three species and the other with low diversity. Out of 273 genera, Taraxacum (12 Species),Astraglus and Cousinia (9 Species each), Artemisia and Silene (8 Species each) and (Bromus 7 Species) were the richest genera. The most extended Chorotype (233 Species, 53%) was related to Irano-Turanian elements (52 Species, 12%) and endemic taxa. The current work showed that the flora of the valley is diverse due to climatic conditions, altidutinal variation, slope and tophography. This study is the first inventory of the valley which provides baseline information for the future prediction regarding plant resources.
Keywords: Flora; Biological spectrum; Chorotype; Terich Valley